Comparative dose-response study of three anticholinergic agents and fenoterol using a metered dose inhaler in patients with chronic obstructive pulmonary disease. Issue 1 (January 1995) - Ikeda, A; Nishimura, K; Koyama, H; Izumi, T
Abstract : BACKGROUND--Inhaled anticholinergics and beta agonists are widely used in the treatment of patients with chronic obstructive pulmonary disease (COPD). However, dosage requirements have not been thoroughly evaluated and comparative dose-response data for these agents are limited. METHODS--Twenty men with stable COPD of mean (SD) age 69.4 (5.8) years and FEV1 0.93 (0.38) litres were studied in randomised, double blind, crossover, placebo controlled experiments. All of the patients received two, four, eight, and 16 puffs of ipratropium bromide (20 micrograms/puff), flutropium bromide (30 micrograms/puff), oxitropium bromide (100 micrograms/puff), fenoterol (200 micrograms/puff), or placebo in random order on five separate days. Doses were administered by a metered dose inhaler at intervals of 60 minutes to give cumulative doses of two, six, 14, and 30 puffs. Five mg of nebulised salbutamol was administered 60 minutes after the patient had received the final 16 puffs of each regimen. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), heart rate, and blood pressure were measured five minutes before each treatment and 30 minutes after treatment with nebulised salbutamol. RESULTS--FEV1 and FVC reached a plateau after administration of a cumulative dose of 14 puffs of ipratropium bromide (280 micrograms) or flutropium bromide (420 micrograms), and after six puffs of oxitropium bromide (600 micrograms). There were no differences with respect to maximum increases in FEV1 and FVC amongst the three anticholinergic agents. However, after six puffs oxitropium bromide produced a greater increase in FEV1 than either ipratropium bromide or flutropium bromide. Fenoterol caused a greater increase in both FEV1 and FVC than the three anticholinergic agents after six puffs, as well as a greater increase in pulse rate. Oxitropium bromide produced a greater increase in pulse rate than the other anticholinergics after 14 puffs. The incidence of side effects was dose-related and notable adverse effects were reported after 30 puffs of ipratropium bromide, 14 puffs of oxitropium bromide, and two puffs of fenoterol. CONCLUSIONS--Oxitropium bromide produced a greater bronchodilator effect than either ipratropium bromide or flutropium bromide when used at doses of less than six puffs, without apparent side effects. There were, however, no differences in maximal response between these drugs. Fenoterol may have a greater peak bronchodilator effect than the anticholinergic agents but it causes more adverse effects, even at lower doses. Depending upon the balance between efficacy and side effects, oxitropium bromide may be preferred in the treatment of patients with COPD.